Interleukin-15 is associated with disease severity in viral bronchiolitis. Issue 1 (5th November 2015) - Leahy, T. Ronan; McManus, Ross; Doherty, Derek G.; Grealy, Robert; Coulter, Tanya; Smyth, Paul; Blackshields, Gordon; Sheils, Orla; Carr, Michael J.; Purandare, Nikhil; Geary, Michael; Hodemaekers, Hennie M.; et al.
Disease severity in viral bronchiolitis in infancy is difficult to predict and has been linked to host innate immunity. The study aimed to investigate the innate cytokine interleukin-15 (IL-15) as a marker of disease severity. A prospective single-centre observational study was conducted in a university-affiliated paediatric teaching hospital, comparing children (0–18 months) hospitalised for viral bronchiolitis, those admitted to the paediatric intensive care unit with severe disease and healthy age-matched controls. IL-15-related parameters were compared between groups. PCR and microRNA (miRNA) sequencing was undertaken on natural killer (NK) cells collected from study participants. Samples from 88 children with viral bronchiolitis and 43 controls enrolled between 2009 and 2012 were analysed. Peripheral blood mononuclear cell (PBMC) IL-15 mRNA expression was significantly higher in those with moderate severity bronchiolitis compared with controls and those with severe disease. Serum IL-15 levels correlated with disease severity. The relative frequency of NK cells in peripheral blood was significantly reduced in participants with bronchiolitis. The NK cell miRNA transcriptome in bronchiolitis was distinct. Targets of de-regulated miRNA were differentially expressed in bronchiolitis, including JAK3, STAT5A and NFKB1 on the IL-15 signalling pathway. IL-15 is associated with disease severity in children hospitalised with viral bronchiolitis. Interleukin-15 influences the host innate response and is associated with disease severity in viral bronchiolitis http://ow.ly/S5JfP